2005
DOI: 10.1590/s1415-54192005000300008
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do uso do Self Etching Primer na colagem de braquetes ortodônticos metálicos

Abstract: Nesta pesquisa laboratorial foi avaliada a resistência de união ao cisalhamento de braquetes metálicos colados ao esmalte dentário bovino, utilizando um sistema adesivo convencional, composto de ácido fosfórico + primer + resina adesiva, e de um sistema SEP (self-etching primer) que combina ácido e primer em uma única solução, avaliado em ambiente seco e úmido (com água). Quarenta e oito incisivos inferiores bovinos foram divididos em três grupos de 16 unidades, que foram assim preparados: grupo 1 (controle) á… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 14 publications
1
9
1
4
Order By: Relevance
“…Other studies using this same kind of material found shearing bond strength with values ranging from 7.5 to 10.57 MPa. 7,18 All results found in this study, including group IV, are near these values (Fig 7). The results indicate that the self-etching system could be used maintaining its characteristic of optimal shearing strength until 9 days after its activation.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…Other studies using this same kind of material found shearing bond strength with values ranging from 7.5 to 10.57 MPa. 7,18 All results found in this study, including group IV, are near these values (Fig 7). The results indicate that the self-etching system could be used maintaining its characteristic of optimal shearing strength until 9 days after its activation.…”
Section: Resultssupporting
confidence: 73%
“…The teeth were selected based on the same criteria adopted by Sponchiado et al 18 and included: Intact enamel surface, absence of prior application of chemical substances such as thymol, hydrogen peroxide, alcohol or formalin. The teeth were cleaned and preserved in distilled water at an average temperature of 4ºC.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations